Social-Ecological Perspectives on Waste Management Behavior: A Case Study in Cisuren Village, Indonesia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Waste management remains a serious environmental challenge in rural areas of Indonesia, particularly in regions characterized by limited infrastructure, difficult geographical conditions, and deeply rooted socio-cultural practices. These conditions shape community perceptions and waste disposal behaviors, potentially generating long-term environmental and public health risks. This study aims to analyze community perceptions and waste management behaviors in Cisuren Village, Lebak Regency, and to identify the socio-ecological factors that influence these practices. The study employs a qualitative descriptive case study design. Data were collected through field observations, in-depth interviews with 10 informants including village officials, community leaders, youth representatives, and local stakeholders therefore document analysis conducted over a six-week period. Data analysis followed an interactive model guided by Social Ecological Theory and Cognitive-Behavioral Theory. The findings indicate that community perceptions are dominated by short-term pragmatic orientations, shaped by limited waste management facilities, hilly geographical conditions with ravines, household economic constraints, and weak institutional support. Practices such as dumping waste into ravines and open burning have become intergenerational habits, while fee-based collection schemes were rejected due to cost considerations. Cisuren Village represents a critical transitional phase in rural waste management. Sustainable change requires an integrated approach that combines the provision of basic infrastructure, environmental education, strengthening of village-level regulations, and multi-level collaboration between communities and government institutions.